The "Machiavellianism" dimension of the Auditor - Aprillia, Lidya; Darmastuti, Dewi (E-Jurnal Akuntansi; Vol 34 No 6 (2024), 2024)
Improving the quality of an external auditor is essential, the auditor has an important role in financial control and supervision. Based on the research carried out, it was found that the dimensions of Machiavellianism   attached to the nature and character of a person can be obscured by ethical and healthy practices, the absence of conflict of interest, and compliance with auditing standards, codes of ethics, procedures, and regulations applicable. By following the ethical codes, auditing standards, and auditing procedures spelt out in this research, both junior and senior external auditors can avoid the machiavellian behaviour that can hurt the results of auditing, the credibility of the profession, the external auditor's credentials, and, of course, many other people just for their own personal gain.    Keywords: Firm Value; Financial Performance; Dividend Policy